The effect of chronic ankle instability (CAI) on Y-balance scores in soccer athlete - Payne, S.; McCabe, M.; Pulliam, J. (The Journal of Sports Medicine and Allied Health Sciences, 2016)
Chronic ankle instability (CAI) is a common problem among athletes and active persons. CAI is an issue that can result from an acute ankle sprain. Individuals are described as having chronic ankle instability if they have had at least one ankle sprain along and suffer residual symptoms for a minimum of one year following the initial ankle sprain and have feelings of instability or "giving way" as well as recurrent ankle sprain incidents.1 Chronic ankle instability has been associated with decreased proprioception and balance sense. Increasingly, the Lower Extremity Y-Balance Test is being used to assess dynamic balance within the athletic population. Maintenance of dynamic balance is very important in athletics due to the amount of movement and coordination that is required.